Zestig jaar vrouwenkiesrecht. Vooraan v.l.n.r. ?, Chapman Catt, Kramers, ?, Manus. Links achter Manus, Jacobs
Zestig jaar vrouwenkiesrecht. Vooraan v.l.n.r. ?, Chapman Catt, Kramers, ?, Manus. Links achter Manus, Jacobs.